2022
DOI: 10.1111/sdi.13052
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between apelin and carotid intima media thickness, and the presence of plaque in dialysis patients

Abstract: Background Apelin is a peptide that has important effects on the cardiovascular system due to its anti‐atherogenic properties and regulating blood pressure. There is not enough research evaluating the effects of apelin levels on the cardiovascular system in hemodialysis (HD) and peritoneal dialysis (PD) patients concurrently. The aim of this study was to determine apelin levels in dialysis, and control groups and to investigate the relationship between apelin and carotid intima media thickness (CIMT). Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the contrary, the detection of serum APLN level in patients on HD and PD indicated that the level of APLN was higher than that in the normal population ( Büyükbakkal et al, 2015 ; Dogan et al, 2018 ). The latest detection of serum APLN levels in patients with PD also indicated that APLN levels in this set of patients were higher than those in the normal population ( Karaer Büberci et al, 2022 ). APLN is mainly catabolized by the angiotensin converting enzyme 2.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the contrary, the detection of serum APLN level in patients on HD and PD indicated that the level of APLN was higher than that in the normal population ( Büyükbakkal et al, 2015 ; Dogan et al, 2018 ). The latest detection of serum APLN levels in patients with PD also indicated that APLN levels in this set of patients were higher than those in the normal population ( Karaer Büberci et al, 2022 ). APLN is mainly catabolized by the angiotensin converting enzyme 2.…”
Section: Discussionmentioning
confidence: 74%
“…However, the relationship between APLN and inflammation, which is known to promote EMT ( Li et al, 2014 ), has been studied. Some scholars suggested that APLN can evaluate inflammation and prevent the occurrence of atherosclerotic cardiovascular disease in patients undergoing both PD and HD ( Dogan et al, 2018 ; Trojanowicz et al, 2020 ; Karaer Büberci et al, 2022 ). However, some studies have also indicated that APLN induces the expression of inflammatory factors MCP-1, VCAM-1, and ICAM-1 in human umbilical vein endothelial cells by activating the NF-kB/JNK signaling pathway ( Trojanowicz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%